2012
DOI: 10.1111/bjh.12129
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial assessing bendamustine plus bortezomib combination therapy for the treatment of patients with relapsed or refractory multiple myeloma

Abstract: Summary Bendamustine, active in multiple myeloma (MM), is a bifunctional mechlorethamine derivative with alkylating properties. Bortezomib, approved to treat MM, is effective in combination with alkylators. The tolerability and efficacy of bendamustine plus bortezomib in relapsed/refractory MM was assessed in an open‐label, dose‐escalating, phase I/II study. Patients aged ≥18 years received intravenous bendamustine 50, 70, or 90 mg/m2 (days 1 and 4) plus bortezomib 1·0 mg/m2 (days 1, 4, 8, and 11) for up to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 47 publications
3
45
0
1
Order By: Relevance
“…A superior response rate of 76 % was reached (PR 28 %, vgPR 24 %, MR 24 %) with a bendamustine, lenalidomide and dexamethasone combination (Pönisch et al 2013). An ORR of 48 % in 40 heavily pre-treated patients (six previous lines of therapy) was reported by Berenson et al (2013) in a phase I/II trial assessing bendamustine plus bortezomib in patients with relapsed or refractory multiple myeloma. OS was estimated at 13.3 months.…”
Section: Discussionmentioning
confidence: 83%
“…A superior response rate of 76 % was reached (PR 28 %, vgPR 24 %, MR 24 %) with a bendamustine, lenalidomide and dexamethasone combination (Pönisch et al 2013). An ORR of 48 % in 40 heavily pre-treated patients (six previous lines of therapy) was reported by Berenson et al (2013) in a phase I/II trial assessing bendamustine plus bortezomib in patients with relapsed or refractory multiple myeloma. OS was estimated at 13.3 months.…”
Section: Discussionmentioning
confidence: 83%
“…Along with others, our group has shown that different doses (1 or 1.3 mg/m 2 ) and schedules (3 or 4 weeks per cycle; Supplementary Table S1) of bortezomib produce similar results when used either as a single-agent or in combination with other agents. 11,12,36 Moreover, although patients may initially be treated at a dose of 1.3 mg/m 2 , many patients require reductions in their dose to 1.0 mg/m 2 , weekly dosing or longer cycles because of toxicity. 37 Overall, the results demonstrate that carfilzomib can safely and effectively replace bortezomib for the treatment of MM patients who progress while on or within 12 weeks of failing a wide range of bortezomibcontaining combination regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib retreatment has been successful for some patients that were previously responsive to this PI, [8][9][10] and for relapsed and refractory MM patients treated with it in combination with other anti-MM agents. 11,12 The ability to overcome bortezomib resistance following retreatment with a different PI has been demonstrated in preclinical studies with bortezomib, carfilzomib, oprozomib (ONX 0912), ixazomib (MLN 9708), delanzomib (CEP-18770) and MLN 2238. For instance, MLN 2238 was shown to induce apoptosis in bortezomib-resistant MM cells.…”
Section: Introductionmentioning
confidence: 99%
“…The ORR in the 31 patients treated with second-line therapy after relapsing from single or double autologous transplantation was 55%. 21 Berenson et al 22 conducted a phase 1/2 trial aiming to establish the MTD of bendamustine in combination with a fixed low dose of bortezomib (1 mg/m 2 ) without corticosteroids in heavily pretreated patients. A dose of 90 mg/m 2 bendamustine given on days 1 and 4 was defined as MTD, but the RR was only 33% and, when MRs were included, 48%.…”
Section: Figure 1 Pfs and Os In Different Patient Cohorts Pfs And Omentioning
confidence: 99%
“…This indicates that bortezomib should be used in the conventional dose of 1.3 mg/m 2 when combined with bendamustine and that corticosteroids should not be excluded from the regimen. 22 Combinations of bendamustine with immunomodulatory drugs have also been evaluated. Thalidomide was combined with bendamustine and prednisone, and reported RRs ranged from 26% in a compassionate use program enrolling highly pretreated patients with a median of 5 prior lines of therapy 23 to 85% in a trial with thalidomide dose escalation from 50 to 200 mg in patients substantially less exposed to previous therapy.…”
Section: Figure 1 Pfs and Os In Different Patient Cohorts Pfs And Omentioning
confidence: 99%